Peran International Criminal Police Organization/ICPO Dalam Kasus Hukum Igor Borbot Tahun 2016 - Benedictus Nugrahanto Kala (Journal of International Relations Diponegoro, 2023)
United States of America and Russia are two countries that have dominant role in world politics. Both countries are frequently found themselves in conflicting relations. Conflicts between United States of America and Russia could be traced from post-World War II Era. The conflicts are varied from ideology, economy, military, even in law enforcement. But there is a unique case, in this case United States of America and Russia were able to conduct law enforcement cooperation assisted by Interpol. How ICPO/Interpol assist this cooperation? Aim of this research is to describe how ICPO/Interpol bridging United States of America and Russia which clearly have many differences on law enforcement system, to conduct a cooperation. Meanwhile a lot of cooperation could not conduct before. This research uses international organization function theory complemented by international organization and international cooperation concepts. Results of this research shows that ICPO/Interpol were able to assist law enforcement cooperation between United States is because it fulfills the functions of informative, normative, law-making, monitoring, and operational.